ANALISIS PENGARUH KUALITAS MAKANAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA PADA BEHAVIORAL INTENTION RESTORAN TOP YAMMIE - Priska Liliani (STIE Wiyatamandala, 2020)
The purpose of this research is to analyze the effect of food quality, service quality on customer satisfaction and its impact on Top Yammie's restaurant behavioral intention. The analytical method used by the authors in conducting this research is to use quantitative research with a total sample of 100 people who are respondents who are people who eat at Top Yammie restaurants. In carrying out the data collection is done by distributing questionnaires in which there are several items of statement. in this study the variables are divided into several parts including food quality (X1), service quality (X2) to customer satisfaction (Y), and behavioral intention (Z). To measure the amount of influence on these variables, the authors use the path analysis method (path analysis). From the results of the analysis it was found that there was a significant influence both partially and simultaneously on food quality variables, service quality on customer satisfaction and its impact on Top Yammie's restaurant behavioral intentions